ANALISIS KARAKTERISTIK HIDROLOGI SUNGAI GAJAHWONG DAERAH ISTIMEWA YOGYAKARTA - Supatno Supatno; Andrea Sumarah Asih (Institut Teknologi Dirgantara Adisutjipto, 2017)
Structuring and technical planning for the development of a watershed requires analysis of hydrological characteristics. This study aimed to analyze the hydrology characteristics of Gajahwong river to be formulated technical effort Gajahwong watershed development. Stages of analysis using secondary data from the Balai PSDA DIY Province, such as watershed maps, daily rain, rain hourly, daily discharge, discharge offlood and flood event records from 2001 to 2013. Analysis of peak flow /flood hydrograph using frequency analysis methods and Collins unit hydrograph methods. While the low-flow analysis using the model HSS Gama I and HS Gama II. The tools used are ArcView, frequency analysis program and Solver are contained in Microsoft Excel. Based on the analysis o f the peak flow of the flood discharge of 20 annual plan obtained 332 m3/ s happened in the 4th hour. While based on a low-flow analysis it can be concluded that during the dry season are still available Gajahwong river flow is sufficient to meet the needs o f well water for irrigation, fisheries and river tours.